PENGARUH PEMBERIAN HORMON TIROKSIN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN BLACK GHOST (Apteronotus albifrons) The effect of giving the thyroxine hormone on growth and survival rate of Black Ghost fish (Apteronotus albifrons) - Dwi Aulia Alwi; Zulkifli Nasution; Khadijah EL Ramija (AQUACOASTMARINE, 2014)
Black ghost fish is a fish which is good economic value, both in the national and international scope. Market demand for the black ghost fish high, so it requires an effort to fulfill consumer demand for the black ghost fish. One of the efforts is to giving stimulation with thyroxine hormone into the commercial feed which is used for the growth of the black ghost fish. This research aims to determine the optimum dose of decent used for the growth and survival of black ghost fish optimally. The tested fish used are black ghost fish size of 6 cm which is maintained in an aquarium sized 60 cm×40 cm×40 cm by 13 units with water volume 24 liters per aquarium arranged randomly. The design which is used was a completely randomized design (CRD) with doses of without treatment, 10 mg/kg, 15 mg/kg, 20 mg/kg and 25 mg/kg. The results showed that the optimum dose which is good for the growth and survival of black ghost fish is 25 mg/kg, which is 4.36 cm long growing from the initial length and weight growth of 4.96 g of initial weight.Keywords: Black Ghost, Thyroxine, Growth, Survival Rate